Representations of the postcolonial city through the eyes of the African artist as Flâneur - Matheolane, Mpho Moses (My University, 2015)
This research report considers the question and concept of the flâneur as an artist and a means of representing the city. In doing this, the figure of the flâneur is removed from its European and Western urban context and placed within an African one. This figure is also imagined as an African black artist as opposed to its popularly and historically known white poet and artist, of Baudelaire’s creation. In this way, the flâneur as an African artist, in an African city, may be used to ask and possibly answer the question of what this all entails for the representation of such a city, are there any differences between this flâneur and its Western archetype? Factoring in the significance of postcolonial theory and its application to space, more especially the city, what nuances and perspectives may be drawn from this? For purposes of the above; the city of Johannesburg is used as the spatial subject matter, the early series of work by the artist Kudzanai Chiurai being an example of the aforementioned representation of the city while the artist himself is seen as the flâneur with the rationale behind his work being the practice of the flâneur that is, flânerie. Keywords: Postcolonialism, postcolonial urbanism, flâneur, flânerie, Baudelaire, Walter Benjamin, Johannesburg, post-apartheid, Achille Mbembe, Kudzanai Chiurai.
Keywords: Postcolonialism; Cities and towns; Urbanization; Sociology, Urban; Africa; South Africa